Comparison between Use of Antibiotics and Argentum (Ag) in Infected Wound Healing - Ismiarto, Yoyos Dias; Husain, Fadlyansyah Farid; Farry, Farry (Faculty of Medicine, Universitas Padjadjaran, 2019)
Infected wound is a common problem encountered in the field of Orthopedics. Various procedures have been applied in order to achieve the effective treatment for wound infection. However, until recently, the biomolecular responses to those remain unclear. This study aimed to compare the effectiveness of antibiotics and argentum in infected wound healing by analyzing the FGF-2 and FGF-7 expressions; fibroblasts; bacteria colonization; and wound contraction rate during the proliferation phase of wound healing. This study was performed from May to September 2016 at the Pharmacology Research Laboratory, Faculty of Medicine, Padjadjaran University. A randomized clinical laboratory experimental trial with repetitive measures was performed in male rabbits that had been wounded and inoculated by 0.5 MF Staphylococcus aureus. Sample was collected before(Day 6) and after (Day 14) the application of antibiotics and argentum. The consecutive sampling method was used to determine the two treatment groups: (I) antibiotic group and (II) argentum group. The argentum group showed higher FGF-2 protein level, FGF-7 protein level, fibroblast count, and wound contraction rate with p<0.05 when compared to the antibiotic group. The use of argentum gave excellent responses to wound repair as indicated by elevated FGF-2 and FGF-7 levels; fibroblast counts; and wound contraction rate. The combination of both treatments might give synergistic responses and better results in healing infected wound. Argentum is more effective than antibiotics to increase the FGF-2 and FGF-7 levels; fibroblasts count; and wound contraction rate in the proliferative phase of infected wound healing. Antibiotics are more effective than argentum to decrease bacteria colonization.Key words: Bacteria colonization, FGF-2 protein, FGF-7 protein, fibroblast count, wound contraction rate Perbandingan antara Penggunaan Antibiotik dan Argentum (Ag) dalam Penyembuhan Luka Terinfeksi Luka terinfeksi sering kali kita temui dalam permasalahan di bidang orthopedi. Berbagai jenis prosedur ditemukan untuk mengurangi angka kejadian infeksi, namun belum sesuai dengan yang diharapkan. Tujuan penelitian ini adalah membandingkan efektivitas antibiotik dengan argentum dengan menilai ekspresi dari FGF-2, FGF-7, fibroblasts dan rerata kotraksi luka saat fase proliferasi penyembuhan luka. Penelitian ini dilakukan selama bulan Juni hingga September 2017 di Laboratorium Penelitian Farmakologi Fakultas Kedokteran Universitas Padjadjaran. Dilakukan pada kelinci jantan yang telah terluka dan diinokulasi oleh Staphylococcus aureus sebanyak 0,5 MF. Sampel diambil hari ke-6 dan ke-14 aplikasi antibiotik dan argentum. Dengan metode sampling berurutan di tiap-tiap kelompok perlakuan: (I) kelompok antibiotik; dan (II) kelompok argentum. Kelompok Argentum menunjukkan tingkat protein FGF-2, protein FGF-7, jumlah fibroblas dan tingkat kontraksi luka yang lebih tinggi dengan p <0,05 dibanding dengan kelompok Ab. Penggunaan argentum memberikan respons yang sangat baik terhadap perbaikan luka seperti yang ditunjukkan oleh peningkatan kadar FGF-2, FGF-7, jumlah fibroblast, dan tingkat kontraksi luka. Kombinasi kedua pengobatan mungkin memberikan respons sinergis dan memberikan hasil yang lebih baik dalam penyembuhan luka yang terinfeksi. Argentum lebih efektif daripada antibiotik untuk meningkatkan kadar FGF-2 dan FGF-7, jumlah fibroblas, dan tingkat kontraksi luka dalam fase proliferatif dari penyembuhan luka yang terinfeksi. Antibiotik lebih efektif daripada argentum untuk menurunkan kolonisasi bakteri.Kata kunci : FGF-2 protein, FGF-7 protein, jumlah fibroblast, kolonisasi bakteri , rata-rata penyembuhan luka